2013
DOI: 10.14260/jemds/932
|View full text |Cite
|
Sign up to set email alerts
|

The Current Scenario of Benign Breast Diseases in Rural India. A Clinicopathological Study

Abstract: To determine the frequencies of various benign breast diseases (BBD) in female patients in Rural India. METHODOLOGY: This is a prospective cohort study of all female patients visiting the surgical clinic with breast problems. This study was conducted at SGT Medical College, Budhera (Gurgaon) India, over a period of about three years starting from March 2010 to February 2013. All female patients visiting the surgical department with breast problems were included in the study. Patients with obvious clinical feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
14
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 8 publications
6
14
2
Order By: Relevance
“…In the present study, two mastitis cases (0.3%) were granulomatous and both were detected in non-menopausal women. These findings were in accordance with other previous studies (Tiwari and Tiwari;Aslam et al, 2013).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the present study, two mastitis cases (0.3%) were granulomatous and both were detected in non-menopausal women. These findings were in accordance with other previous studies (Tiwari and Tiwari;Aslam et al, 2013).…”
Section: Discussionsupporting
confidence: 94%
“…This lesion had mostly occurred within 20-30 years of age, with the mean age at occurrence being 27.9±7.5 years. This findings was in line with that of other studies (Tiwari and Tiwari;DAHRI et al, 2010). Furthermore, fibroadenoma was most prevalent before menopause, which is corresponding with the results of other studies indicating fibroadenoma as the most common breast mass in young women.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…5,12 Tiwari P, also observed fibroadenoma as the predominant lesion in benign breast disease. 13 In this study, common presentation of fibroadenoma cases was lump in the breast (87.5%). Common presentation of fibrocystic disease was pain in the breast (57.5%).…”
Section: Discussionmentioning
confidence: 52%
“…11 Shrestha et al 12 has also reported similar findings stating that tuberculous mastitis is common in females of reproductive age group and rare in males. In another Indian frequency report, Tiwari et al 13 reported 1.77% of tuberculous mastitis cases where 50% were in third decade of life.…”
Section: Discussionmentioning
confidence: 94%